Engineered Liposomes in Interventional Theranostics of Solid Tumors - Kommineni N.; Chaudhari R.; Conde J.; Tamburaci S.; Cecen B.; Chandra P.; Prasad R. (My University, 2025)
Engineered liposomal nanoparticles have unique characteristics as cargo carriers in cancer care and therapeutics. Liposomal theranostics have shown significant progress in preclinical and clinical cancer models in the past few years. Liposomal hybrid systems have not only been approved by the FDA but have also reached the market level. Nanosized liposomes are clinically proven systems for delivering multiple therapeutic as well as imaging agents to the target sites in (i) cancer theranostics of solid tumors, (ii) image-guided therapeutics, and (iii) combination therapeutic applications. The choice of diagnostics and therapeutics can intervene in the theranostics property of the engineered system. However, integrating imaging and therapeutics probes within lipid self-assembly “liposome” may compromise their overall theranostics performance. On the other hand, liposomal systems suffer from their fragile nature, site-selective tumor targeting, specific biodistribution and premature leakage of loaded cargo molecules before reaching the target site. Various engineering approaches, viz., grafting, conjugation, encapsulations, etc., have been investigated to overcome the aforementioned issues. It has been studied that surface-engineered liposomes demonstrate better tumor selectivity and improved therapeutic activity and retention in cells/or solid tumors. It should be noted that several other parameters like reproducibility, stability, smooth circulation, toxicity of vital organs, patient compliance, etc. must be addressed before using liposomal theranostics agents in solid tumors or clinical models. Herein, we have reviewed the importance and challenges of liposomal medicines in targeted cancer theranostics with their preclinical and clinical progress and a translational overview. © 2023 American Chemical Society.